Peran Linguistik dalam Mempelajari Struktur Bahasa Arab - Lulu Najwah Zaid; Wardatul Fitria Utami; Muhammad Rifqi Fauzi; Sahkholid Nasution (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
Linguistics plays a crucial role in studying and understanding the structure of language, including in the context of Arabic. The Arabic language, with its complex system of morphology, syntax, and phonology, requires an in-depth linguistic approach to analyze its grammatical structure. This study aims to explore how linguistic theories, such as phonology, morphology, syntax, and semantics, contribute to understanding the basic structure of Arabic. Through linguistic approaches, a clearer and more structured understanding of sentence structure, word patterns, and the relationships between language elements can be achieved. This paper also discusses the challenges faced in applying linguistic theories to Arabic, as well as the importance of a linguistic approach in teaching Arabic to non-native speakers. The findings of this study are expected to provide broader insights into the role of linguistics in learning and teaching Arabic more effectively and systematically.